Evaluation of Enterococcus faecalis, Staphylococcus warneri and Staphylococcus aureus species in adults with generalized chronic periodontitis - FRITOLI,Aretuza (2017)
ABSTRACT Objective: To identify and quantify the levels of three bacterial species that have recently been identified as potential “new” periodontal pathogens (Enterococcus faecalis, Staphylococcus aureus and Staphylococcus warneri) in subjects with periodontal health and generalized chronic periodontitis. Methods: Thirty adults with generalized chronic periodontitis and 10 periodontally healthy were included in this study. Nine subgingival biofilm samples were collected per subject and individually analyzed by checkerboard DNA-DNA hybridization technique. Results: The mean levels of E. faecalis and S. warneri were higher in chronic periodontitis than in periodontal health (p<0.05). Furthermore, a higher percentage of subjects with periodontitis were colonized by the three species evaluated in comparison with healthy subjects (p<0.05). This represented a difference of 40 percentage points between the two groups, for E. faecalis (present in 90% of individuals with periodontitis and 50% of the healthy individuals) and S. warneri (100% and 60%, respectively), and 26 percentage points for S. aureus (86% and 60%, respectively). Conclusion: E. faecalis and S. warneri have the potential to be periodontal pathogens. The role of S. aureus was less evident, since this species was more prevalent and at relatively higher levels in health than the other two species. These data might guide future studies on the role of these microorganisms in the etiology of periodontitis and help to establish more effective treatments for these infections.